New phenanthroline nickel(II) organodithio-phosphorus complexes: Syntheses, structural characterizations and in vitro cytotoxic activity studies - SAĞLAM, ERTUĞRUL GAZİ (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Seven different dithiophosphonato Ni(II) complexes, [Ni(Xn)(2)], (Xn = (4-MeO-C6H4)PS2(OR) where R = 3pentyl-, X1; R = 1-phenyl-1-propyl-, X2; R = 4-tert-butyl benzyl-, X3; R = diphenylmethyl-, X4; R = 4-tert- butyl cyclohexyl-, X5; R = 3-phenyl-1-propyl-, X6; R = 3-methyl-1-butyl-, X7) and three different dithiophosphinato Ni(II) complexes, [Ni(Yn)(2)], (Yn = (4-MeO-C6H4)PS2(R) where R = 3-methyl-1-butyl-, Y1; R = 2-methyl propyl-, Y2; R = 1-methyl propyl-, Y3) were prepared by the reaction of NiCl2.6H(2)O and the ammonium salts of the corresponding dithiophosphonic and dithiophosphinic acids, [NH4][Xn] and [NH4][Yn], respectively. Starting with these complexes, that were known previously, new organo-dithiophosphonate salts of tris-phenanthroline Ni(II), [Ni(Phen)3][(Xn)2] and organo-dithiophosphinate salts of the same complex, [Ni(Phen)3][(Yn)2], were synthesized and characterized. Structural studies were based on spectroscopic methods (mass spectrometry (ESI), FT-IR, Raman spectroscopy), magnetic susceptibility measurements and elemental analysis. The crystal structures of [Ni(Phen)(3)][(X-1)(2)], [Ni(Phen)(3)][(X-3)(2)], [Ni(Phen)(3)][(X-4)(2)] and [Ni(Phen)(3)][(Y-2)(2)] were determined by single crystal X-ray diffraction analysis. All the complexes were screened against human cell lines for assessing their cytotoxicity. Especially, [Ni(Phen)(3)][(Y-3)(2)] had the highest cytotoxic potency towards the HepG(2) cell line, with an IC50 value comparable to oxaliplatin. Moreover, [Ni(Phen)3][(X1)2]-[Ni(Phen)(3)][(X-3)2(]) were found to have significant cytotoxic activity against the breast cancer cell line with IC50 values of 51.64, 54.19 and 48.58 lM, respectively. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Phenanthroline dithiophosphonate complexes; Phenanthroline dithiophosphinate complexes; Single crystal X-ray analysis; Cytotoxic activity; Antiproliferative activity; Anticancer; NI(II); DFT